Determination of glucose cut-off points for optimal performance of glucagon stimulation test - Kawalec, Joanna; Horzelski, Wojciech; Karbownik-Lewińska, Małgorzata; Lewiński, Andrzej; Lewandowski, Krzysztof C. (Frontiers in Endocrinology, 2024)
The glucagon stimulation test (GST) is widely used to assess growth hormone (GH) and cortisol secretion, nevertheless the precise mechanisms underpinning these hormonal responses remain unclear. We have endeavoured to explore the relationship between glucose and insulin fluctuations during GST and their impact on GH and cortisol secretion.SUBJECTS & METHODS: We retrospectively studied 139 subjects (mean age 35.5±15.1 years, BMI 26.6±6.61 kg/m²), including 62 individuals with a history of pituitary disease (27 with an intact adrenal axis) and 77 healthy controls. Standard dose intramuscular GST was performed in all subjects.RESULTS: Once BMI and age were excluded from multivariate model, the nadir of glucose concentration during GST was the sole variable associated with maximal GH secretion (GH, p<0.0003), while neither glucose/insulin peak, nor glucose/insulin concentrations contributed to GH. 100% pass rate for GH secretion above 3 ng/ml or 1.07 ng/ml cut-offs was observed for glucose concentrations at, or below 60 mg/dl (3.33 mmol/l) (for Controls), or 62 mg/dl (3.44 mmol/l) (for Controls and patients with an intact adrenocortical axis). Such low glucose concentrations were obtained, however, only in about 30% of studied individuals. Conversely, cortisol secretion did not correlate with glucose or insulin fluctuations, suggesting alternative regulatory mechanisms.CONCLUSIONS: This study reveals that glucose nadir below 3.33 mmol/l is the only biochemical biovariable linked with optimal GH secretion during GST, whereas mechanisms responsible for cortisol secretion remain unclear. We emphasize the importance of glucose monitoring during GST to validate GH stimulation and support clinical decisions in GH deficiency management.